Kajian Hukum Dalam Kebijakan Baru untuk Melindungi Kedaulatan Bagi Pelanggar Imigrasi Di Provinsi Bali - Kadek Frediandrika Adnantara (Universitas Tabanan, 2025)
Abstract Legal aspects in the new policy that aims to protect sovereignty in the Province of Bali against immigration violators. As an international tourist destination, Bali faces major challenges in managing immigration issues, including violations of residence permits, illegal activities, and threats to local socio-economic stability. This study analyzes the latest policies issued by the government in enforcing immigration laws, strengthening supervision, and providing strict sanctions to violators. With a juridical-normative approach and policy analysis, this study evaluates the effectiveness of policy implementation and its impact on the protection of state sovereignty. The results of the study show that although the new policy has tightened supervision and provided a deterrent effect, challenges still arise from lack of coordination between agencies, limited resources, and public awareness. Therefore, better synergy is needed between local governments, law enforcement agencies, and the community in implementing this policy in a sustainable manner. This study provides strategic recommendations to strengthen the protection of sovereignty in Bali through a comprehensive and inclusive legal approach. Keywords: immigration law, sovereignty, immigration violations, public policy